Globalization VS Internationalization for Entrepreneurs - Bambang Pratama (Bina Nusantara University, 2011)
In an article in the Harvard Business Review Theodore Levitt published The Globalization of Markets. Business activities across the country after it became a very interesting topic of study for both academics and practitioners. This topic has become so phenomenal because his arguments about globalization is the economic convergence with business activities without any national barriers. In contrast to the internationalization that tends to narrow and tends to do business across national borders. Central idea must answered by manager and entrepreneurs is whether your market global or international. Before answering them it requires understanding and a new paradigm on this matter. Furthermore, Thomas Friedman in his book